KETERWAKILAN KEPENTINGAN MASYARAKAT OLEH DPRD KOTA SURAKARTA DALAM PERUMUSAN PERDA YANG PARTISIPATIF (STUDI KASUS TERHADAP PERUMUSAN PERDA NOMOR 3 TAHUN 2010 TENTANG PENGELOLAAN SAMPAH DI KOTA SURAKARTA) - Sutarno, Anggit Tri pamungkas Pringgo (Educitizen, 2013)
The aim of this research is to find out: (1) City Council of Surakarta performance in arranging Local Regulation No. 3 in the year of 2010 about rubbish management which has not been able to represent people importance can be seen from the content of Clause 36 about prohibition and Clause 46 about Criminal Provision, (2) implementation of the content of Clause 36 about prohibition and Clause 46 about Criminal Provision of the Local Regulation No. 3 in the year of 2010 about Rubbish Management toward people importance.This research used qualitative research with study case method. Research strategy used in this research is single established strategy. Data sources are an informant, place and phenomenon, archive and document. The writer took the sample using purposive sampling. Techniques collecting the data used are interview, observation and document analysis. The writer uses triangulation data and method.  The analysis data uses interactive model such as data collection, data reduction, data presentation, drawing conclusion and verification. Research procedures are preparation, data collection, data analysis, research report arrangement.Based on this research, it can be concluded that: (1) City Council of  Surakarta performance in arranging Local Regulation has not been able to represent people. (2) Impact of the content of Clause 36 and Clause 46 in the Local Regulation toward people importance is there will be people restlessness, people impoverishment, and for City Council Surakarta members, it can make people reduce the trust to them and also can make moral condemnation from the people.